THE ROLE OF THE FISHERMEN’S WIFE IN INCREASING THE HOUSEHOLD INCOME OF THE AKIT TRIBE FISHERMEN IN THE VILLAGE OFBANTANTIMUR BANTAN DISTRICTBENGKALIS REGENCY RIAUPROVINCE - Rohman, Fathur; Zulkarnain, Zulkarnain; Kusai, Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT             Bantan Timur Village, located in Bantan District, Bengkalis Regency, Riau Province, is a coastal area on the South Coast of Sumatra. The village is bordered by the Malacca Strait, the coastal and marine areas in this village also have fisheries and marine potential. So that many fishing communities live in the coastal area of East Bantan Village, and one of them is the Akit Tribe fishing community. to dig up information about the role of fishermen's wives in increasing the household income of Akit fishermen. The method used in this research is survey. This survey method directly observes the object of research, namely the role of fishermen's wives in increasing the household income of Akit tribe fishermen in Bantan Timur Village, Bantan District, Bengkalis Regency. Based on the results of the study, the characteristics of the Akit fishermen's wife are included in the productive age, low education level, the average income of the Akit fishermen's wife working in the salted fish processing sector and the coconut coping under the Bengkalis Regency Statistics Agency (BPS), which is Rp. 1,500,000 / month. The number of dependents of Akit tribal fishing families in Bantan Timur Village Bantan District Bengkalis Regency averages 5-6 people.Keywords: role, increase revenue, fisherman's wife